Implementation of Behavior Counseling with Islamic Shaping Techniques in Overcoming Bullying Behavior of Grade VII Students at MTsN 2 Surabaya City - Alfiani Putri Gardewi; Alincia Dwi Trisnanti; Arif Ainur Rofiq (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
This study aims to explain the application of Behavioral Counseling with Islamic Formation Techniques to reduce bullying behavior among students. Bullying is a serious problem that can hinder the creation of a safe and supportive learning environment. The research method used is descriptive qualitative. The subjects of the study involved seventh-grade students of MTsN 2 Kota Surabaya who were detected to have a tendency to bully behavior. Data were collected through observation, interviews, and documentation from Guidance and Counseling teachers and students who acted as respondents. The results of the study indicate that the application of Behavioral Counseling with Islamic Formation Techniques, which focuses on the gradual formation of positive behavior through reinforcement based on Islamic values, successfully suppressed bullying behavior among students. Therefore, this method can be an appropriate counseling strategy choice to encourage better social behavior in schools